The Application of Problem-Based Learning Model to Improve Students’ Learning Outcomes in Islamic Religious Education Class X SMK PP Negeri Padang Overcome - Agus Mita Rahmi (BiCED Proceeding, 2024)
This study aims to improve the learning outcomes of class X students at SMK PP Negeri Padang Mengatas by implementing the Problem-Based Learning (PBL) model. The PBL model enables students to actively participate in learning through solving contextual problems relevant to everyday life. This approach enhances the effectiveness, creativity, and enjoyment of learning. The results of the study show an improvement in student learning outcomes in each cycle of implementing the PBL model. In the pre-cycle, the passing rate was only 50%, but it increased to 88% by cycle 4. Thus, the implementation of the PBL model is effective in improving learning outcomes in the subject of Islamic Religious Education.